Infection Kinetics and Phylogenetic Analysis of vB_EcoD_SU57, a Virulent T1-Like Drexlerviridae Coliphage - Koonjan, Shazeeda; Seijsing, Fredrik; Cooper, Callum J.; Nilsson, Anders S. (Frontiers in Microbiology, 2020)
The morphology, infection kinetics, genome sequence and phylogenetic characterization of the previously isolated bacteriophage vB_EcoD_SU57 are presented. The phage vB_EcoD_SU57 was isolated on Escherichia coli strain ECOR57 from the E. coli reference collection and was shown to produce four mm clear plaques with halos. Infection kinetics, as assessed by one-step growth analyses, suggest that vB_EcoD_SU57 is a virulent phage with an adsorption rate of 8.5 × 10-10 mL×min-1, a latency period of 14 minutes, and a burst size of 13 PFU per bacterium. Transmission electron microscopy confirmed vB_EcoD_SU57 to be a phage that used to be classified as a Siphoviridae phage. Bioinformatic analyses showed that the genome was 46,150 base pairs long, contained 29 genes with predicted protein functions, and 51 open reading frames encoding proteins with unknown function, many of which were gathered in clusters. A putative tRNA gene was also identified. Phylogenetic analyses showed that vB_EcoD_SU57 is a Braunvirinae phage of the newly formed Drexlerviridae family and closely related to T1-like E. coli phages vB_EcoS_ACG-M12 (Guelphvirus) and Rtp (Rtpvirus) as well as the unclassified phages vB_EcoS_CEB_EC3a and ECH1.